1975
DOI: 10.1182/blood.v46.2.271.271
|View full text |Cite
|
Sign up to set email alerts
|

Energy metabolism in human erythrocytes: the role of phosphoglycerate kinase in cation transport

Abstract: Three models of disturbed erythrocyte metabolism, triose-depleted normal, phosphoglycerate kinase (PGK)-deficient, and pyruvate kinase (PK)-deficient cells, have been studied to examine further the role of PGK in erythrocyte cation transport. Sodium (Na-+) and potassium (K-+) transport were reduced only in cells fully depleted of triose. In such cells the PGK step presumably was inoperative due to total lack of substrate; 2,3-diphosphoglycerate (2,3-DPG) then became the sole substrate source for remaining step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In the preceding Discussion we have indirectly assumed that no compartmentation exists for, as an example, the ATP of the pump. Such compartmentations are possible and have been suggested previously (16,24), but the results obtained in the type of experiments discussed here allow no decision with regard to compartmentation of some glycolytic intermediates.…”
Section: Discussionmentioning
confidence: 70%
“…In the preceding Discussion we have indirectly assumed that no compartmentation exists for, as an example, the ATP of the pump. Such compartmentations are possible and have been suggested previously (16,24), but the results obtained in the type of experiments discussed here allow no decision with regard to compartmentation of some glycolytic intermediates.…”
Section: Discussionmentioning
confidence: 70%
“…Finally, there may be proteins other than glycolytic enzymes that serve as a part of the ATP compartment. Similar schemes were proposed several years ago for functional relationships between the glycolytic enzymes and the Na/K pump (Parker and Hoffman, 1967;Proverbio and Hoffman, 1977;Schrier et al, 1975;Segel et al, 1975). More recently, such a multienzyme system was proposed on the basis of measurements of 31p nuclear magnetic resonances (NMR) of 2,3-DPG and G3P in red cells and bound to IOVs and on an effect ofouabain on the NMR (Fossel andSolomon, 1977 and1979;Solomon, 1978).…”
Section: Discussionmentioning
confidence: 89%
“…It has also been suggested that the ATP synthesized by membrane-associated GAPDH and PGK is compartmentalized in a "membrane pool," which is used preferentially by the Na/K pump (Hoffman and Proverbio, 1974;Okonkwo et al, 1975;Proverbio and Hoffman, 1977). Indirect evidence for the existence of a pump-associated ATP pool was provided by the inhibition of active transport in cells high in ATP, and depleted of triose phosphates (Sachs, 1972;Segel et al, 1975), and the inhibition of the use of a2P-labeled ATP by Na,Mg-ATPase after pretreatment with nonradioactive ATP (Proverbio and Hoffman, 1977). The suggestion of a membrane pool of ATP, however, has met with criticism.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we can consider whether the ghost concentrations of ADP and ATP as referred to in this paper precisely reflect the concentrations of these nucleotides in the immediate proximity of the inner face of the Na/K pump . There is now substantial evidence (Parker and Hoffman, 1967;Okonkwo et al, 1975;Segel et al ., 1975 ;Proverbio and Hoffman, 1977 ;Mercer and Dunham, 1981) indicating that ATP (and ADP) may be compartmentalized within the regional domain of the pump. ATP pooled within this membrane compartment appears to be used preferentially with regard to cytoplasmic ATP as the proximate substrate of the pump .…”
Section: Discussionmentioning
confidence: 99%